2017
DOI: 10.1007/s00360-017-1130-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thermoregulation and monoamine release in freely moving rats during cold exposure and inhibition of the ventromedial, dorsomedial, or posterior hypothalamus

Abstract: The hypothalamus is critical for regulating thermogenesis, but the role of monoamines in specific hypothalamic subregions in thermogenesis is not thoroughly established. The purpose of this study was to confirm changes of body temperature (T ) and thermoregulatory parameters upon inhibition of neural activity in hypothalamic subregions in freely moving rats. In addition, the pattern of monoamine release in these nuclei was measured during active thermoregulation using microdialysis. Tetrodotoxin (TTX) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Antagonism of the 5-HT2AR also reduces body temperature (Pawlyk et al, 2006) and blocks hyperthermic response to social defeat (Sinh and Ootsuka, 2019). Some evidence suggests that exposure to heat or cold increases 5-HT levels (Hale et al, 2011; Ishiwata and Greenwood, 2018; Kelly et al, 2011; Myers and Beleslin, 1971), but other studies found no relationship between temperature manipulations and brain 5-HT levels (Ishiwata et al, 2004; Nakagawa et al, 2016; Saito et al, 2005). We are not aware of any direct evidence showing that body temperature manipulation influences 5-HT2AR activity (Zamfir et al, 1992), but given the intentional manipulation of body temperature in spiritual and therapeutic practice (see below), there are logical reasons to suspect there may be a relationship.…”
Section: Serotonin Stress and The 5-ht2armentioning
confidence: 99%
See 2 more Smart Citations
“…Antagonism of the 5-HT2AR also reduces body temperature (Pawlyk et al, 2006) and blocks hyperthermic response to social defeat (Sinh and Ootsuka, 2019). Some evidence suggests that exposure to heat or cold increases 5-HT levels (Hale et al, 2011; Ishiwata and Greenwood, 2018; Kelly et al, 2011; Myers and Beleslin, 1971), but other studies found no relationship between temperature manipulations and brain 5-HT levels (Ishiwata et al, 2004; Nakagawa et al, 2016; Saito et al, 2005). We are not aware of any direct evidence showing that body temperature manipulation influences 5-HT2AR activity (Zamfir et al, 1992), but given the intentional manipulation of body temperature in spiritual and therapeutic practice (see below), there are logical reasons to suspect there may be a relationship.…”
Section: Serotonin Stress and The 5-ht2armentioning
confidence: 99%
“…As discussed in previous sections, certain types of stress upregulate 5-HT2AR expression and activity (see Table 1 for a review of the relevant literature). Moreover, evidence that acute stress causes the release of 5-HT is compelling (Adell et al, 1997; Amat et al, 1998, 2005; Bastani et al, 2017; Beitia et al, 2005; Bland et al, 2003; Cohen et al, 2015; Ferres-Coy et al, 2013; Fuenmayor and Garcia, 1984; Fujino et al, 2002; Gardner et al, 2005; Hale et al, 2011; Higuchi et al, 2019; Ishida et al, 1997; Ishiwata and Greenwood, 2018; Johnson et al, 2005; Keeney et al, 2006; Kelly et al, 2011; Li et al, 2015; Myers and Beleslin, 1971; Nakajima et al, 2009; Neugebauer, 2020; Paul et al, 2011; Rex et al, 2005; Yoshioka et al, 1995) and it is logical to surmise that increased endogenous 5-HT release will engage the 5-HT2AR system, an assumption backed up by evidence of increased 5-HT2AR associated responses with drug-induced 5-HT release (Kuypers et al, 2018; Liechti et. al., 2000; Pitts et al, 2017; van Wel et al, 2012).…”
Section: The Adaptive Function Of Pivotal Mental Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The VMH is another important nucleus involved in cold-induced thermogenesis, as the activation of the VMH induces BAT thermogenesis in cold-exposed rats 203 and increases oxygen consumption and shivering in rabbits 204 , and chemical lesioning of the VMH causes cold intolerance in rats 205 . Takayuki Ishiwata and colleagues proposed that the VMH is not involved in thermogenesis under cold conditions, with evidence that extracellular noradrenaline, serotonin, and 3,4-dihydroxyphenylacetic acid (DOPAC) levels in the VMH are not changed during cold exposure 206 . However, the data showed that body temperature increase and sympathetic output were reflected through heart rate, while the cold challenge was blocked with the perfusion of tetrodotoxin into the VMH 206 .…”
Section: Hypothalamic Control Of Cold-induced Thermogenesismentioning
confidence: 99%
“…Takayuki Ishiwata and colleagues proposed that the VMH is not involved in thermogenesis under cold conditions, with evidence that extracellular noradrenaline, serotonin, and 3,4-dihydroxyphenylacetic acid (DOPAC) levels in the VMH are not changed during cold exposure 206 . However, the data showed that body temperature increase and sympathetic output were reflected through heart rate, while the cold challenge was blocked with the perfusion of tetrodotoxin into the VMH 206 . In addition, it is debatable whether microdialysis at the level of the lateral VMH can fully demonstrate neurotransmitter release from VMH neurons to downstream target regions, as the VMH does not directly innervate BAT 207 .…”
Section: Hypothalamic Control Of Cold-induced Thermogenesismentioning
confidence: 99%